0123 The impact of sleep, stress, and environmental context on memory pre- and during the COVID-19 pandemic in the United States. (25th May 2022) - Silva-Jones, Jillian; Smith, Anna; Crosswell, Alexandra; Gordon, Amie; Mendes, Wendy Berry; Whitehurst, Lauren
Abstract: Introduction: The COVID-19 pandemic has disrupted the lives of many people. The risk and interpersonal cost of infection as well as the public health measures implemented to mitigate the spread likely have psychological costs. Yet, due to the ever-changing nature of the pandemic, psychological impact has been difficult to capture through research efforts. Here, we leveraged an on-going, geographically representative study to examine the relationship among sleep, stress, and memory function before and during the COVID-19 pandemic. Methods: Participants (N=1958, aged=18+) were enrolled in a 21-day ecological momentary assessment study. All participants provided demographic information, including zipcodes, which were used to identify rural vs urban locale. Participants were instructed to complete up to three daily check-ins during set time windows—morning, afternoon, night--via a phone application. At each morning check-in, participants were asked about sleep duration and quality, and at every check-in, participants reported perceived stress ratings. Participants also completed a paired-associates memory task on Day 2 of the study. For the task, participants were instructed to encode a list of 20 unrelated word and picture pairs. Immediately after encoding, participants were tested on five picture-word pairs. Tests 2 and 3 occurred on a unique set of five words from the initial list three and six days after initial encoding, respectively. Pre- and during COVID assessments were defined as March 2019 to March 2020 and April 2020 to October 2021, respectively. Results: Mixed effects binomial regressions revealed that pre-COVID, longer sleep durations were associated with better memory performance (ß=.09, p<.05), and counterintuitively, higher subjective sleep quality was associated with worse memory performance (ß=-.35, p<.001). During COVID, longer nighttime awakenings were associated with poorer memory performance (ß=-.01, p<.05) and living in a rural vs urban environment was associated with poorer memory performance (ß=.48, p<.01). Older age was associated with worse memory performance pre- and during COVID (ß=-.01, p<.01). Stress was not related to memory pre- or during COVID in these models. Conclusion: Findings support that sleep difficulty before and during the pandemic likely impacts memory function. Additionally, those living in rural U.S. environments may be particularly vulnerable to cognitive changes in the pandemic context. Support (If Any):